Analysis of Mathematical Literacy in Working on Minimum Competency Assessment Questions Reviewed from Adversity Quotient - Aulia Issabilillah, Asa; Mawarsari, Venissa Dian; Suprayitno, Iswahyudi Joko (Education, Science, and Technology International Conference, 2024)
This research is a descriptive qualitative research. School selection in this study used proportionate stratified random sampling technique, as well as sample selection using purpose sampling technique, namely 8th grade students of SMP Muhammadiyah Bumiayu. Data collection techniques in this study were ARP tests, AKM tests, interviews and documentation. The results of the study state that the higher and lower the AQ that students have, it will affect their mathematical literacy skills and the results of working on AKM questions. Climber students will try their best to solve problems related to mathematical literacy. Camper students will try but not optimally. Quitters students give up very easily when solving math problems related to literacy. Based on this analysis, the researcher provides suggestions so that students in the quitter category can be assisted by familiarizing students in interpreting problems, composing solutions with the right procedures so that they can master mathematical literacy skills well. For students who are camper and climber types can be accustomed to solving problems according to the right procedure so that they can master mathematical literacy skills even better.